The impact of input, input repetition, and task repetition on L2 lexical use and fluency in speaking - Duong, Phuong-Thao; Montero Perez, Maribel; Nguyen, Long-Quoc; Desmet, Piet; Peters, Elke (Studies in Second Language Learning and Teaching, 2023)
The present study investigates the impact of meaningful input on L2 learners’ vocabulary use and their fluency in oral performance (immediate and repeat tasks), as well as whether the effects are mediated by learners’ prior vocabulary knowledge and working memory. Ninety university students learning English as a foreign language were randomly assigned to one of three groups: input (N = 29), input repetition (N = 32), and no-input (i.e., baseline group) (N = 29). The input group watched L2 videos prior to performing an immediate oral task, whereas the input repetition group watched the same videos not only before but also after the immediate oral task. The no-input group only performed the oral tasks without watching the videos. The three groups repeated the same oral task after two days. Results did not show a significant effect of task repetition, input, and input repetition on learners’ lexical use and fluency. However, the fluency and lexical complexity in learners’ L2 speech can be predicted by their receptive vocabulary knowledge and working memory capacity to some extent.